2013
DOI: 10.4236/fns.2013.411141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blended Rice Bran and Olive Oil on Cardiovascular Risk Factors in Hyperlipidemic Patients

Abstract: The present study was designed to evaluate the effectiveness of blended rice bran and olive oil on hyperlipidemic subjects. A total of 60 moderately hyperlipidemic patients (Total Cholesterol (TC) >200 mg/dl and/or Triglycerides (TG) >150 mg/dl) with an age range of 45 -60 were selected from Mediciti Hospital of Ludhiana and were divided into two groups: Group A and Group B containing 30 subjects each. The subjects of Group B were given blended rice bran and olive oil for a time period of 45 days and were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Blending of unconventional oils like rice bran, olive, flaxseed and garden cress oils with traditional oils is a good method to take advantage of the ω3 FAs and useful bioactive compounds such as oryzanols and tocopherols present in them (Choudhary et al, 2013; Umesha & Naidu, 2012). Figure 1 illustrates the health benefits of some minor oils.…”
Section: Blending: Need and Benefitsmentioning
confidence: 99%
“…Blending of unconventional oils like rice bran, olive, flaxseed and garden cress oils with traditional oils is a good method to take advantage of the ω3 FAs and useful bioactive compounds such as oryzanols and tocopherols present in them (Choudhary et al, 2013; Umesha & Naidu, 2012). Figure 1 illustrates the health benefits of some minor oils.…”
Section: Blending: Need and Benefitsmentioning
confidence: 99%
“…Similarly, our findings demonstrate that RBO reduced ESR. Scientific research suggests that Phytosterols and linoleic acid content in RBO provide antioxidant and anti-inflammatory effects [74].…”
Section: Rbomentioning
confidence: 99%
“…Similarly, our findings demonstrate that RBO reduced ESR. Scientific research suggests that Phytosterols and linoleic acid content in RBO provide antioxidant and anti-inflammatory effects [74]. Furthermore, our results showed that blood urea nitrogen level was significantly lowered in diabetic patients by 6 months dietary intervention involving consumption of RBO.…”
Section: Rbomentioning
confidence: 50%